Phytochemical evaluation and anti-angiogenic activity of Alingatong (Dendrocnide meyeniana Walp.) root extracts using the chorioallantoic membrane assay on duck embryo - Torno, Ezra Maurel D.; Subebe, Merrah Joy B.; Manting, Muhmin Michael E.; Tabelin, Mylah Villacorte (Penerbit Universiti Kebangsaan Malaysia, 2024)
Dendrocnide meyeniana (Walp.), known as "Alingatong" in the Visayas region of the Philippines, is a plant from the Urticaceae family. It is commonly found in the mountain areas of Taiwan and the Philippines. This study aims to determine the Dendrocnide meyeniana root extract's anti-angiogenic activity. The methanolic extracts of Dendrocnide meyeniana were subjected to preliminary phytochemical screening. Cytotoxicity test using Brine Shrimp Lethality Assay was conducted with different plant concentrations to determine the concentration to use for the anti-angiogenic activity of the root extracts. The anti-angiogenic activity was observed by calculating blood vessel percent inhibition using chorioallantoic membrane assay or CAM assay. Phytochemical screening reveals that the plant contains varying levels of detection of bioactive compounds, including saponins, flavonoids, alkaloids, and steroids. Brine Shrimp Lethality Assay showed that the ethyl acetate and hexane extracts from Dendrocnide meyeniana were highly toxic as their LC50 values were lower than 100 ppm. CAM assay results showed that hexane with 250 ppm concentration has the highest percent inhibition with 34.98% followed by hexane at 125 ppm with 34.07% inhibition. Both concentrations of ethyl acetate showed low percentage inhibition, where 250 ppm was at 19.05% and 125 ppm at 15.93%. One-way ANOVA indicates that the different treatments have significant differences (p-value< 0.0001) in the number of branches present using the CAM assay. Therefore, based on the results, Dendrocnide meyeniana root extracts have anti-angiogenic properties and these findings will help to understand the efficacy of the traditional medicine used by the local people.